IMPLEMENTASI MOTIF GEDOG DALAM DESAIN RANSEL PRIA SEBAGAI SARANA PENGENALAN BUDAYA TUBAN - Pramana, Achmad Bhakti Nusa; Nurhidayat, Martiyadi; Bahri, Nurul Fitriana (Telkom University, 2024)
Tuban is a district in East Java which is located on the coast, with its strategic location making Tuban one of the international trade centers so that many cultures influence people's daily lives. One of Tuban's unique cultural heritage is Gedog batik. Gedog Batik is unique, especially in terms of the fabric making process. By woven traditionally using non-machine looms (ATBM). The distinctive